(untitled) (CIPEEX, 2025)
This study examines the relationship between quality of life, mental health, and academic performance among medical students, considering the intrinsic challenges of the course and external factors such as the COVID-19 pandemic. The integrative review reveals the negative impacts of stress, burnout, and perfectionism, as well as the mitigating role of extracurricular activities, provided they are balanced with academic demands. The study emphasizes the need for psychological and academic support interventions, suggesting that educational institutions adopt a multidimensional approach to improve both the academic performance and well-being of medical students.